Beyond oneness and difference : Li and coherence in Chinese Buddhist thought and its antecedents - Ziporyn, Brook, 1964- (Albany : State University of New York Press, 2013)
"Continues the author's discussion of the development of the Chinese philosophical concept Li, concluding in Song and Ming dynasty Neo-Confucianism"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Li; Philosophy, Chinese; Truth -- Coherence theory; PHILOSOPHY / Eastern; Electronic books